Personal and environment factors and participation as mediators between high school type and school quality of life and wellbeing - Lavie-Pitaro, Yael; Weintraub, Naomi; Golos, Anat (Frontiers in Education, 2025)
IntroductionAlternative schools support students with academic or behavioral challenges through flexible, personalized approaches. These educational environments are closely linked to personal and environmental factors that influence adolescents’ participation in daily activities, which are crucial to their school quality of life (QoL) and wellbeing.MethodsThis study examined the effect of personal and environmental factors and participation as mediators between high school type, school QoL and wellbeing, among 103 students attending alternative schools and 156 peers in traditional schools across Israel.ResultsAlternative school students showed significantly higher motivation and their higher sense of school relatedness approached significance. School type had a positive direct effect on motivation and school QoL. Motivation also mediated indirect effects on out-of-school participation and overall wellbeing. School QoL was shaped by school type, school relatedness, and perceived social support.DiscussionThese findings highlight the effectiveness of supportive, student-centered school environments in enhancing students’ wellbeing, suggesting that incorporating alternative education principles into mainstream settings may improve school QoL and wellbeing.